SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT PADA ANAK-ANAK DENGAN METODE FORWARD CHAINING DI PUSKESMAS ARAS KABU - Susilawati; Fahmi, Hasanul (Jurnal Sistem Informasi Kaputama (JSIK), 2022)
Typhoid is still a disease that is often suffered by people in Indonesia, especially children. But on the other hand the lack of attention from the public to this typhus disease and the lack of knowledge about the early symptoms of typhus causes the general public to be susceptible to the disease. Lack of experts to handle typhus in health centers, especially health centers located far from the city. This of course has an impact on delays in handling patients with typhoid. To overcome this problem, appropriate action is needed to diagnose typhus in these children. An expert system using the Forward Chaining method for diagnosing typhoid in children is the best solution for recognizing the symptoms of typhoid in children as early as possible, knowing the causes of the disease and how to control it. In making this system, it takes experts who are experts in the field of typhus and children to get accurate data regarding information on typhoid in children. This typhoid diagnosis expert system is designed using the web-based PHP programming language. The design of the knowledge base in this system is made dynamically to make it easier to manage data such as adding, changing and deleting data.